THE BETHANY CAVE: A JEWISH-CHRISTIAN CULT SITE? - Taylor, Joan E. (Revue biblique, 1990)
Father E. Testa has proposed the hypothesis that Jewish-Christians venerated a cave in the property of the Sisters of Charity of St. Vincent de Paul, Bethany; but this hypothesis is doubtful. The author re-examines the red drawings of the cave and presents additional information which corroborates her proposition that the cave was known as the Hospitium of Martha and Mary; a Byzantine Christian holy place. Père E. Testa a proposé l'hypothèse que les judéo-chrétiens ont vénéré une grotte dans la propriété des Filles de la Charité de Saint-Vincent de Paul, Béthanie ; mais cette hypothèse est douteuse. L'auteur réexamine les dessins rouges de la grotte et présente des informations additionnelles qui corroborent sa proposition que la grotte a été connue comme le Hospitium de Marthe et Marie ; sanctuaire chrétien byzantin.